The Main Features of Electronically Mediated Communication - Arakelyan, Rouzanna; Hovakimyan, Lilit (Armenian Folia Anglistika, 2013)
It is a fact that the Internet has turned into a unique form of communication nowadays. The language of communication of the internet resembles both the written and oral varieties of speech, however, it must be viewed as a new manifestation of language use which can be defined by a number of spelling, grammatical and semantic features. Despite the existence of common features applying to the electronically mediated language, the internet is a domain of diversity and freedom. The variety of language means used is conditioned by the individuality, sex and even the character of the users. The language of the internet is characterized by the use of abbreviations and clippings, subordinate clauses resembling “stream of consciousness”, a unique spelling, etc. These means aim to speed electronically mediated communication and enhance the emotional-expressive impact.